Mađarsko stanovništvo u NDH – brojčano stanje i proces nestajanja u periodu između 1941. i 1945. - VÉGH, ANDOR (SlavVaria, 2021)
Hungarian population in the Independent State of Croatia – demographic situation and the process of disappearance in the period between 1941 and 1945. Hungarians in Croatia are a minority group in the Carpathian / Pannonian Basin, compared to Hungarians from other neighboring countries, which after 1918 lost most of their members partly by emigration, partly by assimilation. The most intensive disappearances of this minority group from Croatian areas are the decades between the 1931 and 1948 censuses. In this paper, we deal with the issue of emigration and social relations of Hungarians within the borders of the Independent State of Croatia (NDH) and under the administrative area of the National Liberation Army of Yugoslavia (NOV). With the help of archival material, we try to reconstruct those social circumstances of the war years that caused the emigration of a large number of members of this community.